INTRODUCTION TO LABVIEW FPGA FOR RF, RADAR, AND ELECTRONIC WARFARE APPLICATIONS - STRATOUDAKIS, TERRY (ARTECH HOUSE, 2021)
Real-time testing and simulation of open- and closed-loop radio frequency (RF) systems for signal generation, signal analysis and digital signal processing require deterministic, low-latency, high-throughput capabilities afforded by user reconfigurable field programmable gate arrays (FPGAs). This comprehensive book introduces LabVIEW FPGA, provides best practices for multi-FPGA solutions, and guidance for developing high-throughput, low-latency FPGA based RF systems. Written by a recognized expert with a wealth of real-world experience in the field, this is the first book written on the subject of FPGAs for radar and other RF applications.
Keywords: LabVIEW.; LabVIEW; Field programmable gate arrays.; Programmable array logic.; elektronické knihy; electronic books